Elucidation of Relationship between Phytophthora Leaf Blight and Fruit Rot in Tomato - Ghatak, Abhijeet; Ansar, Mohammad; Ghatak, Lajja Vati; Balodi, Rekha (Journal of Postharvest Technology, 2015)
Field experiments were carried out in order to determine the efficacy of traditional and new fungicides for preharvest and postharvest management to late blight disease of tomato. Preharvest management was followed by application of traditional fungicide and combination of fungicides. The combination of Mancozeb with Cymoxanil and Mancozeb with Phenamidone rendered fruit rot incidence between 8.0% and 9.3%, indicating most effective fungicides to manage this disease. Similarly, evaluation of type cultivar (determinate/indeterminate) response was done in the field. This results the intimate relation between infection in leaf and infection in fruit for the determinate cultivars (R2= 0.96). The experiments under high field epidemics (65.0% and 96.5% on leaves and fruits, respectively) have generated preliminary information on relationship between late blight severity on leaves and fruit rot incidence. Our study reveals late blight epidemics both on leaves and on fruits accelerated from the third week of February, which suggests special attention should be taken during this period. The laboratory experiments considered assessment of isolates of Phytophthora, and identification of most virulent isolate of the late blight fungus. Evaluation of infection and its progress on fruits, collected from fungicide treated plots and water sprayed plots, was made. Infection on fruits sampled from the plots treated with previously mentioned combination of fungicides had not progressed significantly (P < 0.05) compared with the fruits collected from plots treated with other fungicides. Occurrence of percent infection was estimated under laboratory in collections of fresh fruit (artificially inoculated) treated with fungicides. Similar result, as exhibited in the field experiments and experiment on infection progress, was obtained from the postharvest study. Postharvest management strategy considering fungicide application is discussed.